Making Public Policies Work: Between Responsiveness and Convergence of Agendas - Luminiţa Gabriela POPESCU (Transylvanian Review of Administrative Sciences, 2011)
This research highlights two concepts: responsive government and policy agenda – as a result of convergence between citizens’ priorities and governmental and parliamentary activity –, and tries to find evidence to prove a relationship of mutual conditioning between the two concepts. The purpose for such a research is justified by the need for a “vision of the future”, a concept devoid of academic rigor and, therefore, difficult to define, but which emphasizes, on one hand, the force of a clear strategic intent and, on the other hand, the irreplaceable role in achieving this vision of public policy to meet the legitimate expectations of citizens. On one side, responsiveness in the context of a system can be defined as an outcome that can be achieved when institutions and institutional relationships are designed in such a way that they are cognizant and respond appropriately to the universally legitimate expectations of the citizens. On the other side, we can detect a policy agenda that represents a common place of convergence between citizens’ priorities and governmental and parliamentary activity. This convergence is a guarantee that the citizens will receive appropriate and opportune responses to their demands. In other words, the convergence agenda involves the existence of a responsive government.